Artificial Intelligence and Organizational Culture: Navigating Contextual Shifts in Structure, Ethics, and Behavior - Areche, Franklin Ore; Ofluoglu, Gokhan (Journal of Organizational and Human Resource Development Strategies, 2025)
This article explores the transformative impact of Artificial Intelligence (AI) on organizational culture. With the increasing integration of AI technologies into business operations, organizational dynamics, decision-making structures, and cultural norms are experiencing significant shifts. This qualitative-descriptive study reviews the literature and synthesizes empirical and theoretical perspectives on how AI reshapes organizational culture, focusing on decentralization, transparency, digitalization, and employee-manager relations. The article also highlights the role of deep learning and artificial neural networks as key technological drivers of this cultural evolution. The results underline the need for adaptive organizational models that integrate AI ethically and strategically.